2016
DOI: 10.1002/2016jd025246
|View full text |Cite
|
Sign up to set email alerts
|

A multisatellite climatology of clouds, radiation, and precipitation in southern West Africa and comparison to climate models

Abstract: Southern West Africa (SWA) has a large population that relies on highly variable monsoon rainfall, yet climate models show little consensus over projected precipitation in this region. Understanding of the current and future climate of SWA is further complicated by rapidly increasing anthropogenic emissions and a lack of surface observations. Using multiple satellite observations, the ERA‐Interim reanalysis, and four climate models, we document the climatology of cloud, precipitation, and radiation over SWA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 87 publications
4
37
0
Order By: Relevance
“…Other studies have indicated that precipitation amount and variability in ERA‐I differs from observational data sets over West Africa (and other areas, e.g., central Africa [ Nikulin et al , ; Sylla et al , ]). Although the large‐scale features of the West African Monsoon are captured, a lack of northward propagation of precipitation results in an ERA‐I overestimation of precipitation along the coast and an underestimation further north [ Diaconescu et al , ; Paeth et al , ; Nikulin et al , ; Hill et al , ]. A weaker first rainfall maxima along the coast [ Diaconescu et al , ; Nikulin et al , ], matched by a shorter first season resulting from the later onset in our results, suggests that this rainfall overestimation is associated with the second wet season.…”
Section: Evaluation Over a Range Of Data Setsmentioning
confidence: 64%
“…Other studies have indicated that precipitation amount and variability in ERA‐I differs from observational data sets over West Africa (and other areas, e.g., central Africa [ Nikulin et al , ; Sylla et al , ]). Although the large‐scale features of the West African Monsoon are captured, a lack of northward propagation of precipitation results in an ERA‐I overestimation of precipitation along the coast and an underestimation further north [ Diaconescu et al , ; Paeth et al , ; Nikulin et al , ; Hill et al , ]. A weaker first rainfall maxima along the coast [ Diaconescu et al , ; Nikulin et al , ], matched by a shorter first season resulting from the later onset in our results, suggests that this rainfall overestimation is associated with the second wet season.…”
Section: Evaluation Over a Range Of Data Setsmentioning
confidence: 64%
“…This behaviour may be linked to the failure of reanalysis products to efficiently represent (in this case underestimate) the northward shift of the WA Monsoon (WAM) as indicated by both Hill et al . () and Thorncroft et al . ().…”
Section: Cloud Cover Variability In Wamentioning
confidence: 98%
“…This is perhaps explained by the difficulty of detecting optically thin cirrus clouds by MODIS as revealed by previous studies (e.g. Lee et al ., ; Sun et al ., ; Hill et al ., ), leading to the lower mean fractions of HCC. The slightly lower values of TCC shown by CERES than ERA5 could be attributed to this same reason but needs to be investigated further.…”
Section: Cloud Cover Variability In Wamentioning
confidence: 99%
See 1 more Smart Citation
“…Since radiation shows distinct diurnal signatures directly linked to the evolution of weather and climate system processes, CERES and geostationary satellite observations have been combined to generate a temporally interpolated data set [ Doelling et al ., , ] that has been used in studies of cloud and aerosol radiative forcing [ Taylor , ; Su et al ., 2013], explaining TOA diurnal cycle variability [ Taylor , ; Dodson and Taylor , ], and to make comparisons with models and reanalyses [ Itterly and Taylor , ; Hill et al ., ]. However, incorporating different geostationary observations with unique sensor characteristics and varying degrees of quality can produce significant artifacts resulting in unnatural spatial patterns in radiation fields [ Doelling et al ., ].…”
Section: Introductionmentioning
confidence: 99%